The internationalization of Knowledge-intensive Business Services Firms (KIBS). - Wu, M; Forsyth, D; D'Souza, N (My University, 2018)
This article provides a review of the literature on international business in the KIBS sector in order to address their internationalization behaviors. The findings reveal that KIBS sectors are talent-intensive, technology-intensive, innovation-intensive, involving co-production with their client firms, and clustered in metropolitans. Knowledge and networks are two important dimensions to their international survival and development. Export and investment foreign entry modes are common in their internationalization. KIBS advance their internationalization with their existing clients and by their own. This paper identifies KIBS as a new unique niche in explaining internationalization behaviors of firms. As current research fails to explain why and how KIBS internationalize, we are calling for more process studies focusing on KIBS internationalization.